Development of models to assess penetrating injury from ballistic projectiles - James, Gregory R. (United Kingdom Defence Academy/Cranfield University, 2020)
Injuries from penetrating ballistic projectiles, such as fragments and bullets, are the major cause of military (and civilian) casualties in conflict, as well as casualties in terrorist incidents. This research project had the primary aim of developing models that facilitate the assessment of injury from penetrating ballistic projectiles, in both a physical and virtual environment. Existing models and literature in this area has been limited to a narrow range of scenarios (such as specific projectile types) or with limited validation of the models. Collation of ballistic data for muscle tissue and simulants from the literature, in addition to an extensive original dataset and novel data analysis techniques allowed a definitive assessment of the validity of skin and muscle tissue simulants for wound ballistics research, relevant to fragments and bullets. A range of physical and virtual models were developed and are applicable to assessing the risk of penetrating projectiles in ballistic and blast scenarios. Considered particularly novel was the development of a new fragment witness pack to assess the hazard from low density and low energy fragments by predicting the risk of eye penetration, skin perforation and to estimate the impact velocity of the projectile. The range of physical and virtual models developed have been used to provide insights to (and describe implications of) the target factors that influence the outcomes of physical testing when using real tissue or tissue simulants. The exploitation of these models has led to improvements in tactics, techniques, and procedures and equipment for UK Armed Forces and police, ultimately reducing injuries and saving lives.
© Crown copyright (2020), Dstl. This material is licensed under the terms of the Open Government Licence except where otherwise stated. To view this licence, visit http://www.nationalarchives.gov.uk/doc/open-government-licence/version/3 or write to the Information Policy Team, The National Archives, Kew, London TW9 4DU, or email: psi@nationalarchives.gov.uk